Effect of the inclusion of L-carnitine on egg quality and productivity of Hy-Line Brown® laying hens - Zelaya, R. L.; Rios, J. J.; Paz, P.; López, S.; Valdiivié, M.; Martínez, Y. (Cuban Journal of Agricultural Science, 2022)
To evaluate the effect of the inclusion of L-carnitine on productivity and egg quality of laying hens, a total of 200 Hy-Line Brown® hens of 85 weeks old were randomly distributed into two treatments, with 20 repetitions/treatment and five hens/repetition for 10 experimental weeks. Dietary treatments consisted of a control diet and the inclusion of 24 mg/kg of L-carnitine. The inclusion of L-carnitine did not change (P> 0.05) laying intensity, food intake, mass conversion and percentage of dirty eggs. However, this experimental treatment (L-carnitine) increased egg weight (63.35 vs. 65.68 g) in relation to control diet (P <0.05). In addition, the inclusion of L-carnitine did not modify (P> 0.05) albumen height, Haugh unit, eggshell strength and yolk color at week 90. However, L-carnitine increased (P <0.05) eggshell thickness with respect to control treatment. At week 95, L-carnitine did not modify (P> 0.05) any indicator of egg external and internal quality. The inclusion of L-carnitine in diets for Hy-Line Brown® laying hens increases egg weight and eggshell thickness at week 90, without significant changes in the other egg quality and productive indicators at week 95 of age. Key words: 3-hydroxy-4-trimethylaminobutyrate, additive, productive indicator, egg modifications, brown layers